Differences in clinical outcomes between traumatic cervical myelopathy and degenerative cervical myelopathy: A comparative study of cervical spinal cord injury without major bone injury and cervical spondylotic myelopathy. (December 2019) - Machino, Masaaki; Ando, Kei; Kobayashi, Kazuyoshi; Morozumi, Masayoshi; Tanaka, Satoshi; Ito, Keigo; Kato, Fumihiko; Ishiguro, Naoki; Imagama, Shiro
Highlights: Residual symptom of traumatic cervical myelopathy (TCM) patients was characterized. Surgical outcomes of degenerative cervical myelopathy (DCM) patients were compared. TCM showed preoperative lower JOA scores for motor function of the upper extremity. Postoperative motor function impairments of the upper extremity persisted in TCM. Motor and sensory function impairments of the lower extremity persisted in TCM. Abstract: A comparative study to examine the surgical outcomes of traumatic cervical myelopathy (TCM) patients was designed. The study aim was to compare the surgical outcomes between TCM and degenerative cervical myelopathy (DCM) and to characterize the preoperative symptoms and postoperative residual symptoms in TCM patients. One hundred consecutive patients with TCM (81 men, 19 women; mean age, 57.7 years; range, 31–79 years) and 100 consecutive patients with DCM (88 men, 12 women; mean age, 58.4 years; range, 36–78 years) were included in this study. All patients were treated by laminoplasty. The pre- and postoperative neurological statuses were evaluated according to the Japanese Orthopaedic Association (JOA) scoring system for cervical myelopathy. The recovery rate (RR) of each function was compared between the two groups. The mean preoperative JOA scores of motor function of the upper extremity in the TCM and DCM groups were 1.9 and 2.3, respectively ( P  < 0.01). After surgery, the mean RRs of motor function of the upper extremity in the TDM and DCM groups were 36.4% and 55.7%, respectively ( P  < 0.01) and in the lower extremity were 32.3% and 46.5%, respectively ( P  < 0.05). The RR for sensory function of the lower extremity was significantly lower in TCM patients than in DCM patients (39.6 vs 68.2, respectively; P  < 0.0001). Motor function impairments of the upper and lower extremities and sensory function impairments of the lower extremities after surgery were more persistent in the TCM group than in the DCM group.